Cause or consequence? Framing and keying mediation in a French secondary classroom. (March 2020) - Joigneaux, Christophe; Rockwell, Elsie
Abstract: In this article, we draw on the commonalities between Vygotsky's emphasis on communication in the 'social situation of development' and Goffman's concepts of framing and keying to analyze a French teacher's mediation between grammatical concepts ciphered in abstract semiotic terms and students' intuitive knowledge of language in use. After describing the context of our broader ethnographic study on French language instruction with immigrant descendant youths in a Parisian secondary school, we examine three types of reframing moves identified in a turn-by-turn analysis of discourse recorded in four lessons on 'cause and consequence' expressions. We show how the teacher continually modulated the discursive texture of classroom mediation to help students navigate the complexity of schooled grammar, while also counting on their intuitive sense of whether the sentences they proposed 'made sense' logically.